Neurovegetative disorders of perimenopausal women treated with docosahexaenoic acid (DHA, 625 mg). (2nd December 2017) - Cianci, Antonio; Maiolino, Luigi; Giunta, Giuliana; Rapisarda, Agnese Maria Chiara; Di Mauro, Paola; Caruso, Salvatore
Abstract: The study evaluated the effect of DHA 625 mg in women who experience menopausal symptoms, on sexuality and quality of life (QoL), and on the auditory brainstem response (ABR). Forty-two perimenopausal women were enrolled. The Kupperman Index (KI) was used to evaluate menopause symptoms. The Short Form-36 (SF-36), Female Sexual Function Index (FSFI), and the Female Sexual Distress Scale (FSDS) were used to assess QoL, sexual function, and sexual distress, respectively. Auditory evoked potentials to measure the ABR. The study had one follow-up at 6 months. The women reported an improvement in the KI total score ( p < .001). Moreover, women reported QoL improvements in all the psychological categories ( p < .001), but not in physical categories ( p = NS). FSFI and FSDS total scores increased ( p < .01) and the FSDS score decreased ( p < .01), mainly due to arousal ( p < .03) and lubrication ( p < .05) sexual aspects. The ABR wave latencies were lower than the baseline values ( p < .05). DHA could be effective in modulating some perimenopausal symptoms in women and, consequently could contribute to improve their QoL and sexual life. Finally, DHA seems to have a direct activity on the neuronal conduction time into the audiological system.